A Historical-Legal Analysis of the Multiple Alien and Nationality Regimes in Force in El Salvador - Serrano-Sánchez, Lucía (2019)
The Salvadoran State, by virtue of the international principle of State sovereignty, submits the migratory flows of people both in and out of the country to the maximum control. All Salvadoran legal instruments of migration and aliens in force today are the result of this maximized control of the population. They are anachronistic legal norms and some of them even pre-constitutional, which do not respond to the current Salvadoran social reality. At the present, an Act is pending for the consolidation of all migration and foreign legislation.